Selection and characterization of recombinant clones that produce Mycobacterium leprae antigens recognized by antibodies in sera from household contacts of leprosy patients. - Hartskeerl, R A (1990)
A Mycobacterium leprae expression library was constructed in the vectors EX1, pEX2, and pEX3 and screened with a pool of 19 well-absorbed sera from household contacts of leprosy patients. Twelve selected recombinants that were further characterized differed clearly from recombinants selected with murine monoclonal antibodies. Whereas the monoclonal antibodies recognized mainly six recombinant antigens, the human sera from contacts reacted with a range of different recombinant antigens. None of the contact recombinant antigens was identical or related to well-characterized antigens from M. leprae or other mycobacteria selected with monoclonal antibodies, including proteins of the heat shock families. Two groups of recombinant antigens could be distinguished: one that was recognized by all sera used in the pool and one that was recognized by only a limited number of sera. These antigens, selected with sera from household contacts of previously untreated lepromatous leprosy patients, may be relevant to the immune responses during the early phase of infection with M. leprae.